Facile method for immobilization of protein on elastic nanofibrous polymer membranes - Roh, Soonjong; Lee, Kangwon; Jung, Youngmee; Yoo, Jin (Frontiers in Materials, 2023)
Surface modification of polymeric scaffolds for biomedical application is a versatile and widely used method to improve interactions between scaffolds and cells. Specifically, chemical immobilization of proteins to polymeric scaffolds provides significant advantages such as stable and biocompatible properties, however, it generally requires expensive instruments or complex steps. In this study, facile method is presented that changes poly(l-lactide-co-caprolactone) electrospun nanofibrous membranes to be cell-friendly and bioactive by chemically immobilization of proteins onto membranes. The model protein, bovine serum albumin was bound onto the nanofibrous membranes via aminolysis and subsequent covalent grafting. The surface modification effects of the nanofibrous membranes including surface morphologies, mechanical properties and wettability were investigated. In addition, in vitro studies have demonstrated that adhesion and proliferation of human dermal fibroblasts are promoted in protein-immobilized membranes compared to bare nanofibrous membranes.